The Role of Visum Et Repertum in Proving Criminal Matters in Indonesia - Tuti Gusmawati Simanjuntak; Lili Rahmayana Harahap; Ahmad Mulia Sembiring (Lembaga Pusat Studi Sosial dan Humaniora [LPS2H], 2024)
The use of Visum et Repertum occurs during the evidentiary stage before a criminal trial. Judges carefully evaluate the robustness of the evidence obtained from this examination, thereby strengthening their confidence in reaching a just verdict. By understanding the important role that the Visum et Repertum plays as a form of evidence, judges are equipped to determine the guilt or innocence of the accused in relation to the alleged crime. The research methodology used is normative legal research, characterized by a descriptive analytical approach. This approach involves a thorough examination of literature sources through various viewpoints, including the Legal approach, Conceptual approach, and Case approach. This research carefully involves primary and secondary legal materials to effectively address the formulation of research problems. Based on the results and discussion, it is known that the importance of visum et repertum (VER) is established as written evidence in accordance with Article 184 of the Criminal Procedure Code. This important component plays an important role in the verdict of serious criminal offenses, including maltreatment, rape, and murder. The findings obtained from a visum et repertum conducted by a qualified expert become an invaluable resource for the presiding judge in determining the applicable charges and the appropriate sentence for the accused. Through the insight provided by a post mortem, one can know the extent of the harm suffered by the victim, both physical and psychological, so as to explain the gravity of the offense in question.